APLIKASI METODE OPTIMASI CENTRAL COMPOSITE DESIGN DALAM FORMULASI SEDIAAN GEL NANOPARTIKEL LIPID DENGAN BAHAN AKTIF 4-n-BUTILRESORCINOL - Ni Kadek Dwi Putri Kusuma Dewi; Rini Dwiastuti (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2022)
Lipid nanoparticle is one of the nanoparticle dosage forms that have a particle size of 1-100 nm. Lipid nanoparticle systems aggregation causes an increase in particle size with storage time so that a carrier is needed that can reduce the aggregation. The lipid nanoparticle system formulated in gel preparations can add to the matrix thereby reducing the aggregation. Central Composite Design (CCD) is one part of the experimental design of Response Surface Methodology that can be used to determine the optimization of gelling agents and humectants in the formulation of lipid nanoparticle gel preparations. The aim of this study was to obtain the optimum composition of carbopol 940 and propylene glycol with the active ingredient 4-n-butylresorcinol using the optimization method of Central Composite Design. This research is an experimental study with independent variables, carbopol 940 and propylene glycol and the dependent variable, the physical properties and physical stability of the gel preparation. The results of this study were carbopol 940 of 0.46 grams and propylene glycol of 9.23 mL were determined as the optimum point obtained from the smallest point in the optimum area using the CCD method.